The Role of Learning Website Integration, Teacher Support, and Student Independence in Enhancing Mathematics Competence at Vocational Schools - Lilis Stianingsih; Ferawati; Fiqih Hana Saputri; Detin Sofia (Information Technology Education Journal, 2025)
Mathematics competence is essential for developing students’ analytical and problem-solving abilities in vocational education. However, many students still face challenges in mastering mathematical concepts effectively. This study aims to examine the influence of Learning Website Integration, Teacher Support, and Student Independence on students’ mathematics competence using a quantitative ex post facto design. The research involved 100 respondents from SMK Bina Mandiri. Data were collected through questionnaires and mathematics competency tests, then analyzed using descriptive statistics and multiple linear regression. The results show that the regression model meets all classical assumption tests and is statistically appropriate for explaining the relationships among variables. Simultaneous testing indicates that all three independent variables significantly influence students’ mathematics competence. Partial testing reveals that each variable has a significant positive effect, with Teacher Support identified as the most dominant factor. The coefficient of determination (R²) is 0.572, meaning that 57.2% of the variation in mathematics competence can be explained by the three variables, while the remaining 42.8% is influenced by other factors outside the model. These findings highlight the importance of integrating technology, strengthening teacher support, and fostering student independence to improve mathematics learning outcomes in vocational education. The results of this study provide guidance for implementing technology-based pedagogy in vocational education.